Przepływy pieniężne według Krajowego Standardu Rachunkowości i Międzynarodowych Standardów Rachunkowości – studium porównawcze - Bereżnicka, Joanna; Franc-Dąbrowska, Justyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The article presents similarities and differences in Cash Flow Account approaches between Polish Accounting Standards and International Accounting Standards (IAS). The analysis show that the approach is not homogeneous and additionally IAS often leaves much space for various interpretations. Additionally IAS recommends to apply the direct method in presenting cash flows from operating activities as more useful, especially in financial planning